Sabías Que… - Alvarado Vázquez, Marco A.; Salcedo Martínez, Sergio M.; Vargas López, Victor Ramón (Universidad Autónoma de Nuevo León, 2024)
En este número se presentan datos poco conocidos acerca de los hongos.